Kinematic effects of the target on the velocity of taekwon-do roundhouse kicks. - Wasik, J.; Mosler, D.; Ortenburger, D.; Góra, T.; Cholewa, J. (Journal of Human Kinetics, 2021)
The phenomena of target kinematic effects under different striking conditions and applying different techniques constitute one of the fields of research for sports biomechanics. However, the influence of some kinematic variables which change under different strike conditions for specific parts of the lower limb remains unknown. The aim of this study was to extend the knowledge on how targets of differen t shapes or the lack of a physical target would affect maximal velocity registered by a marker placed on the foot, knee and hip during the execution of a roundhouse kick. In total, 15 adult males were included in this study. All participants were taekwon-do elite athletes. The displacement of markers placed on the lateral side of the foot, knee and hip during movement execution was registered by a stereophotogrammetry apparatus. Participants performed taekwon-do roundhouse kicks for three target types (into the air, a table tennis ball and a training shield) applying either a sport or a traditional style. The highest maximal velocity was obtained for kicking into the training shield. When applying the sport style, the highest maximal velocity of foot markers for the executed kicks was registered. Kicking into air resulted in higher velocities for proximal body parts than kicking into a tennis ball, but the effect was reversed for the foot marker. In conclusion, a large resistance target is suitable for athletes` motor preparation as it allows the highest maximum velocity to be reached. Small non-resistant targets are recommended for technical training.